PENGARUH PROMOSI TERHADAP BRAND AWARENESS UNTUK MENINGKATKAN MINAT BELI KONSUMEN DI THE BAKERY HOTEL WYNDHAM CASABLANCA JAKARTA - Kusrini, Setiya; Afriasih, Maria Ulfah Catur; Pinandoyo, Dimas Bayu (LPPM Politeknik Pajajaran ICB Bandung, 2024)
Promotion is a key marketing strategy used to communicate product value to consumers. In the hospitality industry, brand awareness significantly affects consumer decision-making. This study aims to examine the effect of promotion on brand awareness and its impact on purchase intention at The Bakery Wyndham Casablanca Jakarta Hotel. Theoretical concepts include promotion as a marketing communication tool and brand awareness as a factor influencing consumer behavior. This research uses a quantitative approach with an associative design. Data were collected from 100 respondents through questionnaires using simple random sampling. Analytical methods include validity and reliability tests, descriptive statistics, and path analysis with SPSS version 25. The results show that promotion positively and significantly affects brand awareness, and brand awareness significantly influences purchase intention. Additionally, promotion indirectly affects purchase intention through brand awareness as a mediating variable. These findings emphasize the importance of consistent and targeted promotion to enhance brand recognition and drive consumer buying decisions. Keywords: Promotion; Brand Awareness; Purchase Intention; Consumer Behavior; Hospitality